If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1.5x + -2 = -0.5x + -2 Reorder the terms: -2 + -1.5x = -0.5x + -2 Reorder the terms: -2 + -1.5x = -2 + -0.5x Add '2' to each side of the equation. -2 + 2 + -1.5x = -2 + 2 + -0.5x Combine like terms: -2 + 2 = 0 0 + -1.5x = -2 + 2 + -0.5x -1.5x = -2 + 2 + -0.5x Combine like terms: -2 + 2 = 0 -1.5x = 0 + -0.5x -1.5x = -0.5x Solving -1.5x = -0.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5x' to each side of the equation. -1.5x + 0.5x = -0.5x + 0.5x Combine like terms: -1.5x + 0.5x = -1x -1x = -0.5x + 0.5x Combine like terms: -0.5x + 0.5x = 0.0 -1x = 0.0 Divide each side by '-1'. x = 0.0 Simplifying x = 0.0
| (y^5x^2)/(y^4x^6) | | z-(-3.3)/3=2.9 | | z-3.3/-3=-2.9 | | 3x-8t=-8 | | 5/6*-6/7 | | 2x+7+10=11x | | 1.7(r+1)=6.8 | | 9-4(2x-1)=45-4x | | (-3-7)+(4+7)= | | -152=4(-8+5m) | | b/9=a | | b/9=8 | | 38n+1=25 | | 3=-4/w-7 | | 3(-5a+9)-2(4a+6)= | | 5.25(2)+3.25=10.25+1.75(2) | | 6x^3-12x^2+10x-20=0 | | -10w+2=2w+18 | | 13x+11=12x+3 | | 2(4x+7)+6x=5(x+10) | | -20+n=3.50 | | (6d+5)-(23d)= | | 5/4-1/3x1/2 | | 11=2x-11 | | -34+2x-7x=76 | | -5x+12=-12x+-12 | | 9-1/3a=-4 | | .25n=-12 | | 2x-9+x+3=-27 | | 4x-3=2(X+13) | | 2x-9+n+3=-27 | | -5x+12=-5x+-12 |